Correlates of Emotional Distress in Out‐of‐Home Youth. Issue 2 (23rd April 2013) - Harpin, Scott; Kenyon, DenYelle B.; Kools, Susan; Bearinger, Linda H.; Ireland, Marjorie
<x xml:space="preserve">Abstract</x> Problem Adolescents in out‐of‐home placement have a high prevalence of mental health distress, and their vulnerability to poor mental health outcomes continues during placement. Risk and protective factors may influence mental health outcomes; however, little is known about their relationship to mental health distress in this population. Methods Using data from a population‐based survey conducted in schools, mental health distress, along with other risk and protective factors, was evaluated in young people who reported living in out‐of‐home placements (n = 5, 516) and a comparison group (n = 5, 500). Multivariate analysis was used to determine the strength of association between risk and protective factors and mental health distress in the youth reporting out‐of‐home placement. Findings Comparisons of risk and protective factors indicated that out‐of‐home youth had greater risks (suicidal risk, mental health distress) and fewer protective factors (feeling parents care about them, other adults care, and school connectedness) than those in the comparison group. Multivariate analyses showed significant associations (38% explained variance) between mental health distress and the risk and protective factors, with the exception of other adult connectedness. Conclusions Findings from this population‐based school survey of young people reiterate that youth in out‐of‐home placements have higher levels of mental health distress and lower levels of protective factors compared to other youth. These results offer insights for those working with out‐of‐home or precariously housed young people.